The Role of Concentration Polarization with Concentration Dependent Diffusion Coefficient in Polymeric Membrane During Pervaporation - Nagy, Endre; Prettl, Zsolt; Hancsók, Jeno; Aurél, Ujhidy (Journal of Membrane and Separation Technology, 2013)
The increase of the diffusion coefficient, due to its concentration dependency, can strongly increase the mass transfer rate through the membrane. Accordingly, the negative effect of the mass transfer resistance of the polarization layer can essentially be increased on the separation efficiency, especially in the case of low solute concentration in the feed phase. This effect can also exist at high solute concentration at extremely high pervaporation rate as it is illustrated by the case study. The simultaneous effect of the concentration polarization and membrane layers is discussed in this paper in case of exponentially or linearly concentration dependent diffusion coefficient. Mass transfer rate, enrichment and the polarization modulus are expressed in implicit, closed mathematical equations involving the transport parameters of the two layers, i.e.the kL, Pe, km, H values. How the increasing diffusion coefficient affects the concentration distribution in the polarization and the membrane layers and due to it, the mass transfer rate, enrichment or the polarization modulus, indicating the effect of the polarization layer, is discussed. It is shown how strongly the dimensionless plasticizing coefficient can decrease the polarization modulus and can affect the concentration distribution in the polarization and the membrane layers as well as the ratio of the diffusion dependent mass transfer rate to that without plasticizing effect, namely if . The case study illustrates the effect of the external mass transfer resistance on the mass transfer rate and on the concentration distribution in the case of high value of a plasticization coefficient.